Radiation-induced hypopituitarism in children with acute lymphoblastic leukemia - Mehrdad Mirouliaei; Masoud Shabani; Fatemeh Bakhshi; Mahtab Ordouei (Indian Journal of Medical and Paediatric Oncology)
Background: Acute Lymphoblastic Leukemia (ALL) is the most common malignancy among children for whom radiotherapy and chemotherapy are used for treatment. When hypothalamus-pituitary axis is exposed to radiotherapy, children′s hormone level and quality of life are influenced. The aim of this study is to determine late effects of radiotherapy on hormonal level in these patients. Materials and Methods: In this study 27 children with ALL, who have been referred to Shahid Ramezanzadeh Radiation Oncology Center in Yazd-Iran and received 18-24 Gy whole brain radiation with Cobalt 60 or 9 MV linear accelerator, were assessed. These patient′s basic weight, height and hormonal levels were measured before radiotherapy and also after different periods of time. Results: GHD (growth hormone deficiency) after clonidine stimulation test was observed in 44% ( n=12) and that in 50% of them ( n=6), less than 1 year, had been passed from their radiation therapy. None of these patients demonstrated hormone deficiency in other axes. Conclusions: This study showed that even application of a 18-24 Gy radiation dose might influence growth hormone levels; therefore, we recommend reduction of radiotherapy dose in such patients whenever possible.